EFEK BERKUMUR DENGAN EKSTRAK TEH HIJAU 3% DALAM MENINGKATKAN pH SALIVA - Hervina, Hervina (Faculty of Dentistry, Mahasaraswati Denpasar University, 2017)
Buffering capacity of saliva plays a very important role in maintaining the saliva pH. The saliva pH affected by the mechanical and chemical stimulation of the oral cavity such as rinse with 3% green tea extract. The purpose of this study is to know the increased of saliva pH after rinsing with 3% green tea extract for three minutes. Experimental research using pre test-post test control group design was conducted on students and patients at Dentistry Hospital Faculty of Dentistry Mahasaraswati University. 44 samples divided into four groups by simple random sampling technique. The average of saliva pH post rinsing with distilled water for three minutes 6,74+0,13; 3% Green tea extract for one minute 6,81+0,12; two minutes 6,96+0,13 and three minutes 7,12+0,12. Analysis by One Way Anova test showed p= 0,000, this means that after the treatment was given to all group, the saliva pH were significantly different. LSD test showed that the increased saliva pH after rinsing with 3% green tea extract for three minutes were higher than one minute and two minutes. The Conclusion is rinsing with 3% green tea extract for three minutes increases saliva pH.